HOW EFL LEARNERS PERCEIVE GRAMMAR IN SPEAKING AND WRITING - Afi Normawati (STKIP Persada Khatulistiwa Sintang, 2023)
Studies about grammar have been conducted by many researchers. As an essential aspect of communication, grammar is closely related to the mastery of language skills, including two productive skills: speaking and writing. This research addresses how EFL learners perceive grammar in speaking and writing. The study involved the fourth-semester students of English Education Department of Universitas Tidar. An open-ended questionnaire was used to gather information on their opinions on the significance of grammar in speaking and writing. The result shows that in writing, EFL learners value grammar as a crucial aspect; therefore, they focus on grammar when they produce written text. Meanwhile, in speaking, some learners believe that grammar is important so that they take notice of grammar when they speak, but other learners regard it as not crucial and they do not pay attention to its usage when they communicate. This finding is interesting since in EFL learning context, learners’ perception on the role of grammar in speaking and writing is important to the success of the language learning itself.